Brood amalgamation in surf scoters Melanitta perspicillata and other Mergini - Savard, Jean-Pierre L; Reed, Austin; Lesage, Louis (Wildfowl, 1998)
Brood amalgamation is frequent within the Tribe Mergini. We quantified amalgamation in the Surf Scoter (Melanitta perspicillata) by a combination of observations on marked and unmarked broods at Lake Malbaie, Qu bec. Brood amalgamation was frequent, especially when brood density was high. Broods, amalgamated or not, were always tended by a single female. Lone females sometimes associated with broods for short periods of time, but occasionally threatened and attacked young. Most often, lone females were chased off by the attending female. Females with young did not try to attract other young and were quite aggressive towards strange young. No behaviour suggesting any voluntary abandonment of young by females was observed. Brood amalgamation in this population apparently occurred accidentally, presumably favoured by crowding, a variable level of aggressiveness between females and apparently weak female-young bonds. A review of the literature on brood amalgamation in the tribe Mergini supports these findings.